Power factor control of solar photovoltaic inverter as a solution to overvoltage - Faizura Norhasmi N.N.; Raveendran S.K.; Ramachandaramurthy V.K. (IEEE Computer Society, 2023)
Computer software; Electric inverters; Electric power factor; Electrolysis; Greenhouse effect; Photovoltaic cells; Power control; Renewable energy resources; Solar concentrators; Distribution systems; Over-voltages; Power factors; Reliability and safeties; Renewable energy systems; Solar photovoltaic inverters; Solar photovoltaic system; Voltage profile; Solar power generation